Temporal fermentation and microbial community dynamics in rumens of sheep grazing a ryegrass-based pasture offered either in the morning or in the afternoon - R.E. Vibart; S. Ganesh; M.R. Kirk; S. Kittelmann; S.C. Leahy; P.H. Janssen; D. Pacheco (Animal, 2019)
Eight ruminally-fistulated wethers were used to examine the temporal effects of afternoon (PM; 1600h) v. morning (AM; 0800 h) allocation of fresh spring herbage from a perennial ryegrass (Lolium perenne L.)-based pasture on fermentation and microbial community dynamics. Herbage chemical composition was minimally affected by time of allocation, but daily mean ammonia concentrations were greater for the PM group. The 24-h pattern of ruminal fermentation (i.e. time of sampling relative to time of allocation), however, varied considerably for all fermentation variables (P⩽0.001). Most notably amongst ruminal fermentation characteristics, ammonia concentrations showed a substantial temporal variation; concentrations of ammonia were 1.7-, 2.0- and 2.2-fold greater in rumens of PM wethers at 4, 6 and 8h after allocation, respectively, compared with AM wethers. The relative abundances of archaeal and ciliate protozoal taxa were similar across allocation groups. In contrast, the relative abundances of members of the rumen bacterial community, like Prevotella 1 (P=0.04), Bacteroidales RF16 group (P=0.005) and Fibrobacter spp. (P=0.008) were greater for the AM group, whereas the relative abundance of Kandleria spp. was greater (P=0.04) for the PM group. Of these taxa, only Prevotella 1 (P=0.04) and Kandleria (P<0.001) showed a significant interaction between time of allocation and time of sampling relative to feed allocation. Relative abundances of Prevotella 1 were greater at 2h (P=0.05), 4h (P=0.003) and 6h (P=0.01) after AM allocation of new herbage, whereas relative abundances of Kandleria were greater at 2h (P=0.003) and 4h (P<0.001) after PM allocation. The early post-allocation rise in ammonia concentrations in PM rumens occurred simultaneously with sharp increases in the relative abundance of Kandleria spp. and with a decline in the relative abundance of Prevotella. All measures of fermentation and most microbial community composition data showed highly dynamic changes in concentrations and genus abundances, respectively, with substantial temporal changes occurring within the first 8h of allocating a new strip of herbage. The dynamic changes in the relative abundances of certain bacterial groups, in synchrony with a substantial diurnal variation in ammonia concentrations, has potential effects on the efficiency by which N is utilised by the grazing ruminant.